PEMANFAATAN LUMPUR SIDOARJO SEBAGAI BAHAN SUBSTITUSI AGREGAT PADA PEMBUATAN BATA BETON - , Slamet Setiyono ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Lusi was Lumpur Lapindo mudflow in Sidoarjo is a generation that have been occurred since 2006 until now is still not overflow can be overcome, in reduction just make dam overflow for Lusi not extensive. Of the impact has been widespread equivalent 3 villages resulting social, authors in this case impartially to anyone just trying to provide alternative ideas to the parties - parties involved to take advantage of such as material substitution Lusi sand in the manufacture of non-structural concrete. From the results of previous studies found that the chemical content Lusi does not include hazardous materials. So the researchers tried to use as a sand replacement material. By way destroy chunks of Lusi and filtered ASTM sieve size 10 (2mm) and sand mixed with a ratio of 1:4 (4 sand weight : 1 cement weight) while the mixture with a composition Lusi is 20%, 30%, 40%, 60 %, 80% of the total sand. For pressure variations in the manufacture are made with pressure 50kg, 75kg, and 100 kg, while at the Lusi mixture of 80% at a pressure of 100kg hard mold is formed because it is very sticky to the molder. From the results of this study authors found that Lusi may be made of paving bloks with SNI standard strength with a certain ratio. One ought to this is one of the solutions in reducing the overflow Lusi and can be marketed to the public.